Pathophysiological substantiation of medical evacuation of the wounded persons, suffering injuries of the extremities on the levels of medical support - І. P. Khomenko; S. О. Коrol; B. V. Маtviychuk; L. А. Ustinova (Клінічна хірургія)
Onbjective. To determine the optimal scheme of medical evacuation for the wounded persons, suffering the combat trauma of the extremities, bаsing on clinic-statistical analysis of changes in the homeostasis indices.